The Cross-Generations Response of Indonesian Muslimsto Ideological Issues in Online Media - Setianto, Widodo Agus (UI Scholars Hub, 2021)
This study aimed to provide an overview of the Muslims’ responses across generations to ideological issues related to Communism, LGBT and radical Islam in online media. The response to ideological issues by the Moslems is important because Islam is the majority religion in Indonesia. The responses from Muslims to the issues of Communism, LGBT, and radical Islam will determine the continuity of the Islam in Indonesia. The theories applied in this study were theory of the media role as agents of production, reproduction and distribution of knowledge to society; media influence mechanisms; and reception theory about the audience’s response to a stimulus. The research method used the reception analysis method. Data analysis was carried out through three main elements, namely: data collection, data analysis, and data interpretation. This data analysis involved three categories of responses, i.e. dominance, negotiation, and opposition and analysis of their social context. The results showed that the four categories across generations had different acceptance responses to the issues studied. The issue of Communism received a dominant acceptance response by the Baby Boomer generation and gen X, while gen Y and Gen Z were in opposition. For LGBT issues, the Baby Boomers, Gen X, Gen Y and Gen Z were all in opposition. For the issue of radical Islam, the Baby Boomers were in negotiations, while the Gen X was in opposition. Meanwhile, Gen Y and Gen Z were dominant. The digital native and digital immigrant generations both had a dismissive response to the LGBT issues. The digital native generation had good acceptance of the communism and radical Islam issues, while the digital immigrant generation rejected the communism and radical Islam issues. The environment and social interactions affected the respondents’ response to the ideological issues they received through online media. Studi ini bertujuan untuk memberikan gambaran respon umat Islam lintas generasi terhadap isu-isu ideologis yang berkaitan dengan Komunisme, LGBT dan Islam radikal di media online. Respons terhadap isu-isu ideologis oleh umat Islam penting karena Islam adalah agama mayoritas di Indonesia. Tanggapan umat Islam terhadap isu Komunisme, LGBT, dan Islam radikal akan menentukan keberlangsungan Islam di Indonesia. Teori-teori yang diterapkan dalam penelitian ini adalah teori peran media sebagai agen produksi, reproduksi dan distribusi pengetahuan kepada masyarakat; mekanisme pengaruh media; dan teori penerimaan tentang respons audiens terhadap stimulus. Metode penelitian menggunakan metode analisis penerimaan. Analisis data dilakukan melalui tiga elemen utama, yaitu: pengumpulan data, analisis data, dan interpretasi data. Analisis data melibatkan tiga kategori respon, yaitu dominasi, negosiasi, dan oposisi dan analisis konteks sosial mereka. Hasil penelitian menunjukkan bahwa keempat kategori lintas generasi tersebut memiliki respons penerimaan yang berbeda terhadap isu-isu yang diteliti. Isu Komunisme mendapat respon penerimaan yang dominan oleh generasi Baby Boomer dan Gen X, sementara Gen Y dan Gen Z bertentangan. Untuk isu LGBT, generasi Baby Boomers, Gen X, Gen Y dan Gen Z semuanya berseberangan. Untuk masalah Islam radikal, para Baby Boomers memilih bernegosiasi, sementara Gen X bertentangan. Sementara itu, Gen Y dan Gen Z dominan. Generasi digital native dan digital immigrant sama-sama memiliki respons meremehkan isu LGBT. Generasi digital native memiliki penerimaan yang baik terhadap masalah komunisme dan Islam radikal, sementara generasi digital immigrant menolak masalah komunisme dan Islam radikal. Lingkungan dan interaksi sosial mempengaruhi respons responden terhadap isu ideologis yang mereka terima melalui media online.